2020
DOI: 10.7196/samj.2020.v110i12.15270
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopy practice in South Africa: The way forward

Abstract: This open-access article is distributed under Creative Commons licence CC-BY-NC 4.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…The Adherence Determinants Questionnaire (ADQ), a survey instrument developed by DiMatteo and colleagues to measure patient self-adherence to cancer prevention interventions and cancer treatments, was administered to all study participants [ 15 ]. The choice of survey instrument was well suited to our study since colonoscopy is an important tool used for diagnosing colorectal cancer in our setting [ 1 ]. The ADQ consists of seven elements, which were identified by DiMatteo et al, as being related to patient adherence to recommendations for both the prevention and treatment of cancer: Interpersonal aspects of medical care received, beliefs around the severity of cancer, beliefs around the perceived utility of the recommended treatments, subjective norms regarding adherence, intentions to adhere to the recommended treatments, and the presence of supports and absence of barriers to adherence [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Adherence Determinants Questionnaire (ADQ), a survey instrument developed by DiMatteo and colleagues to measure patient self-adherence to cancer prevention interventions and cancer treatments, was administered to all study participants [ 15 ]. The choice of survey instrument was well suited to our study since colonoscopy is an important tool used for diagnosing colorectal cancer in our setting [ 1 ]. The ADQ consists of seven elements, which were identified by DiMatteo et al, as being related to patient adherence to recommendations for both the prevention and treatment of cancer: Interpersonal aspects of medical care received, beliefs around the severity of cancer, beliefs around the perceived utility of the recommended treatments, subjective norms regarding adherence, intentions to adhere to the recommended treatments, and the presence of supports and absence of barriers to adherence [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Diagnostic colonoscopy is the method of choice for investigating lower gastrointestinal disease pathologies [ 1 , 2 ]. A finalised report from a diagnostic colonoscopy, including the histopathology findings from any biopsies performed, will not be available on the day of the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…36 A study from South Africa reported that for an uninsured population of 50 million persons, only 70,000 colonoscopies were performed annually in the public health sector. 35 In Pakistan, a country with an average annual income of $650 and no national health insurance system, a colonoscopy costs $100 which is prohibitively expensive. 37…”
Section: Colonoscopymentioning
confidence: 99%
“…33 Screening colonoscopy for CRC is rare in LMICs due to the lack of human resources and equipment as well as financial constraints. 34 35 A WHO report showed that only Antigua and Barbuda, and Colombia from the Americas region had screening colonoscopy in their CRC screening guidelines but these were only done opportunistically rather than through systematic population-based screening programs. 36 A study from South Africa reported that for an uninsured population of 50 million persons, only 70,000 colonoscopies were performed annually in the public health sector.…”
Section: Colorectal Clinical Practice In Low- and Middle-income Count...mentioning
confidence: 99%